Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex]y=3x+13 \\
2x=y-9 \ \ \ |-y-2x \\ \\
y=3x+13 \\
\underline{-y=-2x-9} \ \ \ \hbox{add the sides} \\
y-y=3x-2x+13-9 \\
0=x+4 \\
x=-4 \\ \\
y=3x+13=3 \times (-4)+13=-12+13=1 \\ \\
\boxed{(x,y)=(-4,1)}[/tex]
y = 3x + 13
y = -2x + 9
2y = x + 22
2y = x + 22
2 2
y = 1/2x + 11
1/2x + 11 = 3x + 13
-1/2x -1/2x
11 = 2 1/2x + 13
-13 - 13
-2 = 2 1/2x
-2 = 2 1/2x
2 1/2 2 1/2
-0.8 = x
y = 3(-0.8) + 13
y = -0.24 + 13
y = 12.76
(x, y) = (-0.8, 12.76)
y = -2x + 9
2y = x + 22
2y = x + 22
2 2
y = 1/2x + 11
1/2x + 11 = 3x + 13
-1/2x -1/2x
11 = 2 1/2x + 13
-13 - 13
-2 = 2 1/2x
-2 = 2 1/2x
2 1/2 2 1/2
-0.8 = x
y = 3(-0.8) + 13
y = -0.24 + 13
y = 12.76
(x, y) = (-0.8, 12.76)
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.